KONTRIBUSI KEKUATAN OTOT LENGAN BAHU DAN KOORDINASI MATA TANGAN DENGAN KETERAMPILAN SMASH FOREHAND DALAM PERMAINAN TENIS MEJA CLUB KITOGALO - Yuni Astuti Dwi Ningsih; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was conducted with the aim to determine the contribution of shoulder arm muscle strength and hand eye coordination with smash forehand skills in the club kitogalo. The problems found in this study are the strength of the shoulder arm muscles and eye hand coordination are still inaccurate and less directional, it is seen when an athlete performs a table tennis forehand smash, still looks less maximal and directed as a result the ball is easily blocked by the opponent. This research was carried at club kitogalo. This research was conducted from February to July 2020. The sampling technique used in this study was total sampling, in which a total population of 6 people was selected as a sample. Based on the results of the study that the author has described in the previous chapter, the following conclusions can be drawn: "There is a significant contribution simultaneously between the strength of the shoulder arm muscles and hand eye coordination with the smash forehand skills in club kitogalo table tennis". Where the results obtained from the calculation of the determinant coefficient, there is a contribution between the strength of the shoulder arm muscles, with smash forehand skills with a yield of 2,56%. And there is a contribution between eye-hand coordination with the results of smash forehand skills with 25% results. Furthermore, it means that there is a contribution between the strength of the shoulder arm muscles and eye-hand coordination with the smash forehand skill with a contribution of 25%.Key Words: Arm-Shoulder Muscle Strength, Hand Eye Coordination, Smash Forehand Skills